Multiple Members of the UDP-GalNAc: Polypeptide N-Acetylgalactosaminyltransferase Family Are Essential for Viability in Drosophila - Tran, Duy T. (American Society for Biochemistry and Molecular Biology, 2012)
Mucin-type O-glycosylation represents a major form of post-translational modification that is conserved across most eukaryotic species. This type of glycosylation is initiated by a family of enzymes (GalNAc-Ts in mammals and PGANTs in Drosophila) whose members are expressed in distinct spatial and temporal patterns during development. Previous work from our group demonstrated that one member of this family is essential for viability and another member modulates extracellular matrix composition and integrin-mediated cell adhesion during development. To investigate whether other members of this family are essential, we employed RNA interference (RNAi) to each gene in vivo. Using this approach, we identified 4 additional pgant genes that are required for viability. Ubiquitous RNAi to pgant4, pgant5, pgant7, or the putative glycosyltransferase CG30463 resulted in lethality. Tissue-specific RNAi was also used to define the specific organ systems and tissues in which each essential family member is required. Interestingly, each essential pgant had a unique complement of tissues in which it was required. Additionally, certain tissues (mesoderm, digestive system, and tracheal system) required more than one pgant, suggesting unique functions for specific enzymes in these tissues. Expanding upon our RNAi results, we found that conventional mutations in pgant5 resulted in lethality and specific defects in specialized cells of the digestive tract, resulting in loss of proper digestive system acidification. In summary, our results highlight essential roles for O-glycosylation and specific members of the pgant family in many aspects of development and organogenesis.